Ectopic Pregnancy Following Levonorgestrel Emergency Contraception: Report of Two Cases - Telbiyska, Katia; Angelova, Mariya (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract Ectopic pregnancy (EP) is likely to occur as an unwanted complication after unprotected intercourse in spite of levonorgestrel emergency contraception (LNG-EC). Its incidence has been increasing recently. We present 2 cases of tubal EP after the oral use of levonorgestrel, treated by laparoscopy.The first unruptured EP with unclear ultrasound findings, because of uterine ventrofixation after the caesarean section (CS) . The second case is a ruptured EP after LNG –EC on day 24 of the period with mild haemoperitoneum with severe peritoneal irritation. The fundamental question is whether levonorgestrel participates in the etiology of EP. The etiology of EP involves many factors. Levonorgestrel mechanisms of action give us grounds to believe theoretically that it increases the risk of EP and participates as an etiological factor.